ESSENTIAL PRINCIPLES OF VIOLIN INTERPRETATION - Cătălina GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
Many people tend to consider musical tonality as a gift of nature. Of course, we cannot deny its influence; however, in the interpretation of any beginner violinist, even of the most talented ones, tonal musicality is not something that appears from the start. It perfects itself throughout a long process of development of the interpretative knowledge. During the performance of a musical piece, any musician – regardless of whether he/she is a pianist, violinist or vocal singer, uses a full and profound sound that beautifies the interpretation and gives it more musicality, more feeling, warmth and spirituality. In order to render the character of a musical piece during interpretation, it is not enough to possess only the dynamic and timbral source (though it is important, of course), but still it is necessary to find a high quality sound that would coincide with the style, character and content of that particular piece.